2021
DOI: 10.1186/s13550-020-00737-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implementation of PLANET® Dose for dosimetric assessment after [177Lu]Lu-DOTA-TATE: comparison with Dosimetry Toolkit® and OLINDA/EXM® V1.0

Abstract: Background The aim of this study was to compare a commercial dosimetry workstation (PLANET® Dose) and the dosimetry approach (GE Dosimetry Toolkit® and OLINDA/EXM® V1.0) currently used in our department for quantification of the absorbed dose (AD) to organs at risk after peptide receptor radionuclide therapy with [177Lu]Lu-DOTA-TATE. Methods An evaluation on phantom was performed to determine the SPECT calibration factor variations over time and to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
6
15
0
Order By: Relevance
“…Lesion volumes were not affected by changes in registration, but the gating process from DDG reduces volume. The typical amount of volume decrease observed in this study was larger than, but still similar to, previous work on DDG-PET [ 11 , 25 , 26 , 35 ]. The larger changes in volume observed in this work may result from this study’s selection bias—only prospectively identified cases with clinically relevant misregistration.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Lesion volumes were not affected by changes in registration, but the gating process from DDG reduces volume. The typical amount of volume decrease observed in this study was larger than, but still similar to, previous work on DDG-PET [ 11 , 25 , 26 , 35 ]. The larger changes in volume observed in this work may result from this study’s selection bias—only prospectively identified cases with clinically relevant misregistration.…”
Section: Discussionsupporting
confidence: 88%
“…Some prior DDG-PET studies have typically noted an approximate increase in SUV max of 10% from the DDG process [ 11 , 25 , 35 ], whereas in another study the DDG-PET method most closely resembling ours used here led to an approximate increase of 20% [ 15 ]. A very recent study that used the same DDG-PET method as here, but with an EE breath-hold CT protocol, found very similar increases in SUV max as observed here for DDG-PET (~ 25%) [ 26 ].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations